(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
The economy of Uzbekistan has been developing rapidly in recent years, and foreign direct investment plays an important role in this process. The importance of foreign investments in ensuring economic stability of the country, creating new jobs and ensuring technological development is incomparable. Foreign direct investment accelerates economic growth by attracting new capital and resources to the economy of Uzbekistan. In 2023, the economy of Uzbekistan grew by 5.5%, the contribution of foreign investments was large in this indicator. New investments allow to increase production and create new products. Foreign investments create many new jobs. In 2023, more than 100,000 new jobs will be created in Uzbekistan based on foreign investments.